2023
DOI: 10.54097/ije.v2i2.7773
|View full text |Cite
|
Sign up to set email alerts
|

Research on oil and gas production prediction process based on machine learning

Abstract: In recent years, the development trend of artificial intelligence is getting better and better. It has been widely used not only in the fields of big data analysis, automobile automatic driving, intelligent robot and face recognition, but also in various fields of oil and gas industry. Oil and gas production prediction is an important part of reservoir engineering, which is very important for the future production and development of strata, and can give developers some development suggestions. At present, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The stress sensitivity coefficients were obtained from the core experiments in the study area, and the experimental results showed that the correlation between stress sensitivity coefficients and the permeability was good, which can be expressed by Equation (17).…”
Section: Modeling Of Production Capacity Of Vertical Wells Containing...mentioning
confidence: 99%
See 1 more Smart Citation
“…The stress sensitivity coefficients were obtained from the core experiments in the study area, and the experimental results showed that the correlation between stress sensitivity coefficients and the permeability was good, which can be expressed by Equation (17).…”
Section: Modeling Of Production Capacity Of Vertical Wells Containing...mentioning
confidence: 99%
“…The third is the analytical or semi-analytical capacity model [13][14][15] based on physical assumptions, which is derived with rigorous ideas, but the current model cannot reasonably characterize the actual seepage characteristics of heavy oil reservoirs, and it is more difficult to apply at the mine site. The fourth is the simulation-based method [16,17], usually using numerical simulation software to predict the production capacity. This method can consider the effects of multiple factors on the production capacity, but it depends on the computational power, model accuracy, and input data accuracy, which is relatively cumbersome.…”
Section: Introductionmentioning
confidence: 99%